Investigation of Several Biomarkers Associated with Diabetic Nephropathy - Jiang, Z. S.; Jia, H. X.; Xing, W. J.; Han, C. D.; Wang, J.; Zhang, Z. J.; Qu, W. (Experimental and Clinical Endocrinology & Diabetes, 2015)
Objective: The aim of this study was to facilitate the systematic discovery of diagnostic biomarkers of diabetic nephropathy (DN).Methods: 3 publicly available independent cohorts were got from Gene Expression Omnibus database. Gene expression array were used to screen for genome-wide relative significance (GWRS) and genome-wide global significance (GWGS). The most significant up- and down-regulated top 100 gene signatures were identified using a fold change based model. Then the protein-protein interaction (PPI) network was constructed, while the hub genes in this PPI network were identified by centrality analysis. Modules detection was performed to explore the functions of the modules. Meanwhile, gene enrichment analysis was performed to illuminate the biological pathways and processes associated with DN.Results: The most significant up- and down-regulated top 100 gene signatures were identified and a PPI network was established. Several hub genes (VEGFA, IL8, MYC, CD14, ALB) were discovered. Several functional modules were revealed. Biological pathways including cytokine-cytokine receptor interaction and p53 signaling pathway, and processes including inflammatory response, response to wounding and enzyme linked receptor protein signaling pathway were identified.Conclusion: Our study displayed underlying biomarkers including biological pathways and several hub genes of DN.
Keywords: diabetic nephropathy; hub genes; bioinformatics